CHANGES BASED ON OXIDATIVE STRESS IN METOLACHLOR AND ATRAZINE TREATED MAIZE SEEDLINGS - Canakci-Gulengul, Songul; Kirecci, Oguz Ayhan; Karabulut, Fadime (Pakistan Botanical Soc, 2019)
The present study investigated biochemical effects of Atrazine (0, 200 mu M, 500 mu M and 1000 mu M) and Metolachlor (0, 100 mu M, 500 mu M and 1000 mu M) concentrations applied to 15-day-old seedlings of three maize varieties (Zea mays L., cv. Saccharata, cv. Danona, and cv. Advanta 2898) for 48 hr. Hydroponic environment was preferred for all treatments for the seedlings. Compared to their controls, GSH/GSSG ratio was decreased, SOD activity was increased, and CAT activity was also decreased/decreased in root/leaf of Atrazine treated maize seedlings. While % ratios of fatty acids in leaf was increased for palmitic acid and palmitoleic acid in cv. Saccharata and advanta 2898, but was decreased in cv. Danona. While the rate of linoleic acid was increased in leaves in other two ratios but decreased only in cv. Saccharata; linoleic acid was increased only in cv. Saccharata and decreased in others. Compared to their controls, in root/leaf of maize seedlings treated with Metolachlor; GSH/GSSG ratio decreased/increased, SOD activity decreased/increased, and CAT activity decreased/decreased. While % ratios of fatty acids in leaf showed an exceptional increase and increase for linolenic acid, palmitic acid, and linoleic acid; palmitoleic acid and stearic acid decreased and palmitic acid decreased only in cv. Advanta 2898. Generally, the inhibitive effect of the herbicides Atrazine and Metolachlor elevated in parallel to increased dose (1000 mu M). However, Atrazine displayed a more oxidative damagesthan Metolachlor on three maize varieties.
Keywords: Maize (Zea mays L.); Oxidative stress; Atrazine; Metolachlor; Herbicides